Integrasi Pendidikan Karakter dalam Mata Kuliah Bahasa Indonesia untuk Menyiapkan Mahasiswa Menghadapi Dunia Kerja di Politeknik LP3I Makassar: Penelitian - Husni Bt Salam (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Vocational education demands graduates who excel not only in technical skills but also possess character traits that meet the needs of the workplace. As a vocational education institution, LP3I Makassar Polytechnic faces challenges in preparing students to be highly competitive, particularly in discipline, responsibility, integrity, and professional communication. This study aims to analyze the integration of character education into Indonesian language courses as an effort to shape students with character and competence in facing the workplace. The research method used a descriptive qualitative literature review by examining journal articles, books, and institutional documents related to the curriculum and industry needs. The results of the study indicate that Indonesian language courses can be a strategic vehicle for instilling character values ​​through project-based learning, collaborative discussions, and academic literacy assignments. The integration of character education into Indonesian language learning has proven relevant to improving LP3I students' work readiness, particularly in terms of communication skills, professionalism, and work ethics.